Trust and Workplace Performance - John T. Addison; Paulino Teixeira (Institute of Labor Economics (IZA), 2019)
This study explores the relationship between trust and establishment performance. The outcome indicators are management's assessment of the economic or financial situation of the workplace and its relative labor productivity. Trust is initially measured using the individual survey respondent's assessment of the 'contribution' of the other side, the rating of the employee representative being favored over that of management as less subject to feedback from performance. Although the potential endogeneity of employee trust is taken into account, an improved measure is constructed from the discrepancy or dissonance between the assessments of the two sides as to the quality of industrial relations at the workplace. All trust measures are associated with improved establish-ment performance. However, there is no suggestion from specifications using the two more favored trust measures that any one type of formal workplace representation – either works councils or union bodies – is superior. Dissonance, if indeed exogenous, demonstrates that good industrial relations trump type of workplace representation.
Keywords: J50; 330; trust; dissonance; workplace employee representation; economic/financial performance; labor productivity